Treatment of affective dysregulation in ADHD with guanfacine: study protocol - Waltereit, Johanna; Uhlmann, Anne; Tarassidis, Christos; Preuss, Ulrich; Roessner, Veit; Waltereit, Robert (Frontiers in Child and Adolescent Psychiatry, 2025)
The early onset, high prevalence, persistence and comorbidity of developmental disorders make affective dysregulation (AD) in childhood and adolescence one of the conditions with the greatest psychosocial burden and economic impact on society. Despite ongoing research, there remains a substantial need to optimize individualized treatment strategies to improve treatment outcomes and alleviate subjective distress and economic costs. The objective of this study is to investigate psychopathological markers of AD in children and adolescents with attention-deficit/hyperactivity disorder (ADHD) treated with the drug guanfacine as part of routine clinical care. These ADHD patients typically have not responded adequately to methylphenidate or other stimulant treatment. This study will employ a multicenter, single-arm design to evaluate the effects of guanfacine on AD symptoms in n = 40 patients of children and adolescents receiving regular ADHD treatment. The findings of this study are expected to address the hypothesis that guanfacine provides beneficial effects on symptoms of AD in addition to its effects on symptoms of ADHD. Public clinical trial registryAffective Dysregulation (AD) in Children With ADHD Treated by Guanfacin, ClinicalTrials.gov ID NCT04016207.